زيارةدراسيةلميادين الأنثروبولوجياالعربية - بلخيري, سليمة (Changement Social, 2018)
The anthropology as a science nascent and especially in the Arab world is in a seriousattempt to study the physical and cultural characteristics and immaterial to thesecommunities as one of the countries that have sufferedfrom the remnants of colonialism, itisalsotrying on the one hand to experience the cultural and value changes that are occurring in the world in the framework of the so-called cultural invasion value system resultingfromscientific and technologicaldevelopment and urges involving prescription globalization. It has become the main concern of manyanthropologistsArabresearchers to work on the establishment of an ArabAnthropology and investthem to seeArab society better, Through the above, youcansaythat the contemporaryArabresearcherswere able to provide a historicallegacy of accomplishment of quantity and quality in the fields of religious, political, economic and otherfields of anthropology in the Arabanthropology hand, weseekthroughthispaper to address the followingproblem: Whatis the reality of Anthropology in the Arab country, and what are the most important areas thataccounted for anthropologicalstudieswhere?